(untitled) (GEOmedia, 2025)
The first EUSATfinder Advisory Board (AB#1) took place in Île-Rousse, Corsica, on 1 July 2025, bringing together first responders, institutions, and technology providers to discuss the role of space, aerial, and terrestrial assets in crisis management. Central to the debate was the integration of Europe’s flagship programs: GOVSATCOM for secure communications, Copernicus for Earth observation, and Galileo for positioning and timing. Operational insights from Italian and French agencies showed how drones, satellites, and advanced monitoring systems are already transforming disaster response, while also exposing needs for reliable communication, rapid data sharing, and user-friendly platforms. Industry and research partners presented innovative tools ranging from AI-powered decision support to geospatial intelligence platforms. At its core, the EUSATfinder project seeks to deliver secure, integrated communications, enabling beyond visual line of sight drone missions, mobile operational centers, and citizen applications. The project will be further demonstrated in Rome in November 2025 and in the Aosta Valley in 2027.